Curso técnico em enfermagem : análise do processo de formação e suas contradições - Reis, Ednilton Pereira dos (2016)
In this thesis we will discuss the process of formation of the nursing technician taking into account the possible contradictions that affect such formation. We aim to answer how the nursing technician training is in relation to the conditions of the course offering, taking into account the following variables: pedagogical political project, teachers and students. The criticism which is made to professional qualification of the nursing technicians is presented on the basis of social, political and economic determinants that have influenced the teaching and the practice of nursing in the country as well as the laws and rules that regulate the activities of technical education. The research is characterized itself from the fundamentals of qualitative research and it has as its data collection instrument the documental analysis and questionnaire. The research subjects were the coordinators, teachers and students of a nursing technical course. The hypothesis we point is that the formation of the nursing technician is marked by contradictions and it seeks to meet the training for the labor market without prioritize the referenced training that articulate the several knowledge dimensions. This study is organized into three chapters that deal with the project of the current society; legal system about the training of nursing technicians and finally with the analysis of what was collected, reflecting the reality of the nursing technicians formation.